Die invloed van Ernst Bloch op die Politieke Teologie van Johann Baptist Metz - Hofmeyr, Murray (HTS teologiese studies, 2003)
The influence of Ernst Bloch on the Political Theology of Johann Baptist MetzThis article deals with the decisive influence that Ernst Bloch had on the young German Catholic theologian during the 1960s, as he grew progressively dissatisfied with the categories of Rahner’s anthro-pological or transcendental theology. It is argued that Bloch’s influence is to be understood more in terms of his modern Jewish Messianism than his Marxism. Through his intense friendship with Bloch. Metz rediscovered the Jewish traditions that have been suppressed in Catholic Christianity. He gained the courage to confront the certainties of his own theological tradition with his unreconciled experiences of non-identity. Bloch taught Metz to appropriate eschatology as belonging to the centre of Christianity, to relate transcendence and future, and to clarify the relationship between human praxis and future as transcendence. But such eschatology operates with a problematical concept of praxis.